SPK Pemberian Pinjaman Menggunakan Metode AHP dan SAW (Studi Kasus KSP Bhina Raharja Purbalingga) - Nicolaus Teguh Santoso; Yohanes Suhari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Cooperative is a business entity or organization owned and operated by its members to fulfill common interests. The Savings and Loans Cooperative Bina Raharja Purbalingga is one of the savings and loans cooperative located in the city of Purbalingga. In providing loans, many criteria must be considered when making decisions by cooperative management. Of course this can be difficult for cooperative management to make decisions. Based on this, to facilitate cooperatives in making decisions, a decision support system is needed. The decision support system that will be developed uses the AHP and SAW methods. This study shows that the results of the calculations using the AHP and SAW methods are not much different, namely alternative 1, alternative 2, and alternative 4 are eligible to get a loan. While alternative 3 does not meet the feasibility.